2020
DOI: 10.1186/s13550-020-00622-4
|View full text |Cite
|
Sign up to set email alerts
|

[18F]Atorvastatin: synthesis of a potential molecular imaging tool for the assessment of statin-related mechanisms of action

Abstract: Background: Statins are lipid-lowering agents that inhibit cholesterol synthesis and are clinically used in the primary and secondary prevention of cardiovascular diseases. However, a considerable group of patients does not respond to statin treatment, and the reason for this is still not completely understood. [ 18 F]Atorvastatin, the 18 Flabeled version of one of the most widely prescribed statins, may be a useful tool for statin-related research. Results: [ 18 F]Atorvastatin was synthesized via an optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 77 publications
0
6
0
1
Order By: Relevance
“…Solvent gradient was as follows: 0–4 min, 90% A; 4–15 min, 90% A to 20% A; 15–25 min, 20% A to 5% A; 25–33 min, 5% A; 33–34 min, 5% A to 90% A; 34–35 min, 90% A; flow, 6 mL·min –1 ; R t ≈ 16 min. Finally, solid-phase extraction allowed for the exchange of solvents, and [ 18 F]atorvastatin was obtained in a physiological and injectable calcium acetate solution 15 (0.05 M pH 7.0) in <10% ethanol.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Solvent gradient was as follows: 0–4 min, 90% A; 4–15 min, 90% A to 20% A; 15–25 min, 20% A to 5% A; 25–33 min, 5% A; 33–34 min, 5% A to 90% A; 34–35 min, 90% A; flow, 6 mL·min –1 ; R t ≈ 16 min. Finally, solid-phase extraction allowed for the exchange of solvents, and [ 18 F]atorvastatin was obtained in a physiological and injectable calcium acetate solution 15 (0.05 M pH 7.0) in <10% ethanol.…”
Section: Experimental Sectionmentioning
confidence: 99%
“… 16 , 17 Atorvastatin also seems to have a particular propensity for pleiotropic effects, which may be related to its lipophilicity. 18 20 Preliminary in vitro evaluations from our group 15 showed that [ 18 F]atorvastatin retains the specific binding to HMG-CoA reductase of the conventional drug and shows increased uptake in atherosclerotic plaques (approx. 2:1) with respect to healthy vascular tissues.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Основным эффектом статинов является снижение эндогенного синтеза холестерина путем ингибирования печеночной гидроксиметилглутарил (HMG) CoA-редуктазы, стадии, ограничивающей скорость мевалонатного пути производства холестерина [4]. Наряду с этим одним из наиболее важных эффектов терапии статинами является поддержание стабильности атеросклеротических бляшек [5].…”
unclassified